Characterization of C1q-binding material released from the membranes of Raji and U937 cells by limited proteolysis with trypsin. - Erdei, A (1988)
C1q-binding material was released, by limited proteolysis with trypsin, from the membranes of intact cells of the Raji lymphoblastoid cell line and the U937 monocytic cell line. The trypsin-digested C1q-binding material was purified from the supernatant of the trypsin-treated cells by affinity chromatography on C1q-Sepharose followed by gel filtration. On gel filtration in non-dissociating conditions this material behaved as a molecule of approx. Mr 65,000, while on SDS/polyacrylamide-gel electrophoresis two peptides of Mr 10,000 and Mr 15,000 were seen under both reducing and non-reducing conditions. Evidence for the synthesis of the C1q-binding material by both Raji and U937 cells was obtained by biosynthetic-labelling studies using [35S]cysteine and [35S]methionine.